2000
DOI: 10.1046/j.1464-5491.2000.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance alone does not explain the clustering of cardiovascular risk factors in southern India

Abstract: Insulin resistance is not the only underlying factor for the clustering of CVD risk factors in south Indians. These findings are consistent with the presence of several distinct physiological domains, as shown in other ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
1
8

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
6
26
1
8
Order By: Relevance
“…Despite the subjective nature of factor analysis and differences as to which variables are included, results of these studies have shown some consistency. Many of them, like the present study, have identified a four-factor solution with factors representing obesity, insulin-glucose metabolism, lipid metabolism, and blood pressure, with some minor variation in composition of individual factors (7)(8)(9)(10)(11)(12). Others have identified a three-factor solution that combines some of these entities; commonly, obesity is combined with lipid and/or insulin variables (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Despite the subjective nature of factor analysis and differences as to which variables are included, results of these studies have shown some consistency. Many of them, like the present study, have identified a four-factor solution with factors representing obesity, insulin-glucose metabolism, lipid metabolism, and blood pressure, with some minor variation in composition of individual factors (7)(8)(9)(10)(11)(12). Others have identified a three-factor solution that combines some of these entities; commonly, obesity is combined with lipid and/or insulin variables (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 57%
“…Thus, factor analysis is well suited for identifying components of the metabolic syndrome, and several analyses have been undertaken for this purpose (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Prospective epidemiological studies of factor "scores" from these analyses can further determine relations between components of the metabolic syndrome and incidence of diabetes.…”
mentioning
confidence: 99%
“…8 The ATP III report considers insulin resistance as one of the three underlying factors for the MetS, the others being obesity and 'independent factors'. 7 Multiple studies seeking to clarify the underlying etiology of the MetS have detailed anywhere from two to four factors independently associated with the MetS [9][10][11] These clusters invariably include insulin resistance but also include factors ranging from obesity to hyperglycemia. Recently, an underlying inflammatory process has been linked to the MetS and postulated as an explanation for the association of MetS with CVD.…”
Section: Conceptual Basis Of the Metabolic Syndromementioning
confidence: 99%
“…These studies have invariably found more than one factor and usually 3-4 factors clustering independently. [9][10][11] For example, Hanley et al 9 identified two factors underlying the metabolic abnormalities comprising the MetS using factor analysis. One was termed a 'metabolic' factor, with positive loadings of BMI, waist circumference, fasting and 2-h glucose, and TG and inverse loadings of insulin sensitivity…”
Section: Differences In the Clustering Of Metabolic Parameters In Difmentioning
confidence: 99%
“…Abdominal obesity is a strongly concluded phenotypic companion for a cluster of metabolic abnormalities characterized by insulin resistance [4,5]. However, the association with abdominal obesity and features of the metabolic syndrome has been reported to vary with gender [6,7], and with different degrees of obesity [8,9]. Although abdominal obesity is the best obesity-related predictor of Correspondence: Ulf Lindblad, Community Medicine, Department of Clinical Sciences, Malmö University Hospital, SE-205 02 Malmö, Sweden.…”
mentioning
confidence: 99%